Associations Between Substance Use in Commission of Sexual Crimes and Offense Characteristics Among Youth: Mitigating Effects of Substance Use Treatment. (February 2018) - Yoder, Jamie; Caserta, Deborah A.
The small extant research base on substance use and youth sexual offending has very few descriptive details. Furthermore, research has yet to test associations between the use of substances in the commission of sexual crimes and offense-related characteristics and how substance use treatment can mitigate these effects. In a sample of residentially housed youth adjudicated of a sexual crime ( N = 332), prevalence patterns are broken down by type of substance use behavior. Sequential regression models are run to test the associations between substance use prior to a sexual crime and number of victims, sexual deviance, and non-sexual criminality. Substance use treatment is tested as a mitigating factor in these relationships. Results reveal high levels of family substance use, and high rates of alcohol, marijuana, and other substance use. There were associations between substance use prior to sexual criminality and sexual deviance and non-sexual criminality. Substance use treatment reduced the effects of substance use on non-sexual criminality. Research and treatment implications are offered.